PENGUATAN PERPUSTAKAAN PADA GERAKAN LITERASI SEKOLAH DI SMPN 18 PADANG - Ratnawita Ratnawita; Fauza Masyhudi; Rendy Nugraha Frasandy; Alfurqan Alfurqan (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This study aims to explain the strengthening of the library in the school literacy movement at SMP Negeri 18 Padang. The research method used is a qualitative descriptive method with a single instrumental case study approach because the researcher collects detailed information collected using various data collection procedures over a continuous period of time, which explores in-depth information related to literacy at SMPN 18 Padang. The results showed that there were 2 (two) roles of libraries that were strengthened in the school literacy movement at SMP Negeri 18 Padang, namely the role of libraries as information providers and the role of libraries as managers of student reading materials which must be supported by adequate information technology.